2018
DOI: 10.5194/os-2017-100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics of Chromophoric and Fluorescent Dissolved Organic Matter in the Nordic Seas

Abstract: 25Optical properties of Chromophoric (CDOM) concentrations in the study region, and the slope coefficient (S 300-600 ) shows some promise to 53 be used. 54Ocean Sci. Discuss., https://doi

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 1 publication
(1 reference statement)
2
25
1
Order By: Relevance
“…Pavlov et al () investigated CDOM dynamics in Kongsfjorden (West Spitsbergen), lately dominated by advection of AW, and demonstrated that CDOM in surface layer is primarily of autochthonous origin with properties comparable to AW in the WSC. Observations reported by Makarewicz et al () in Nordic Seas revealed significant year‐to‐year variability in CDOM absorption associated with variable interplay of cold and low‐salinity water from the Sørkapp Current and intensity of AW inflow.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…Pavlov et al () investigated CDOM dynamics in Kongsfjorden (West Spitsbergen), lately dominated by advection of AW, and demonstrated that CDOM in surface layer is primarily of autochthonous origin with properties comparable to AW in the WSC. Observations reported by Makarewicz et al () in Nordic Seas revealed significant year‐to‐year variability in CDOM absorption associated with variable interplay of cold and low‐salinity water from the Sørkapp Current and intensity of AW inflow.…”
Section: Introductionmentioning
confidence: 85%
“…A detailed description of water masses in the study region has been presented by Makarewicz et al (), who modified Rudels et al () classification to better represent local solar heating and the corresponding decrease in potential density of AW (at salinity >34.9). In summer 2013, 2014, and 2015, the study area was dominated by two water masses: AW that occupied depths below 60 m and Polar Surface Water warm (PSWw; Figure ), from surface to 60‐m depth.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations